A STUDY ON THE UTILIZATION OF RAINWATER HARVESTING FOR RAW WATER NEEDS IN A CAMPUS AREA - Achmad Achmad Rafi'ud Darajat; Muhammad Amin; Ali Murtopo (Universitas Udayana, 2025)
One of the Sustainable Development Goals (SDGs) is to ensure universal access to clean water. However, in practice, the availability of clean water often faces both quality and quantity challenges. Rainwater harvesting presents a viable alternative source of raw water that can be optimized to meet these needs. Preliminary observations at Universitas Tidar revealed that collected rainwater exhibited high turbidity levels and iron (Fe) content exceeding the quality standards set by the Indonesian Ministry of Health Regulation No. 32 of 2017. This study was conducted in the campus area of Universitas Tidar to evaluate the effectiveness of various activated carbon media thicknesses and contact times in improving rainwater quality. The treatment system utilized a Vertical Flow Roughing Filter (Upflow type) consisting of zeolite gravel, activated carbon, silica sand, volcanic sand, and a water filter housing unit. Three different thickness variations of activated carbon were tested. The results demonstrated significant improvements in water quality, particularly in reducing turbidity and iron content. The best performance was observed at the 60th minute using an 80 cm thickness of activated carbon, achieving 93% turbidity reduction and 99% iron removal efficiency. Based on these findings, the treated rainwater meets sanitation standards and can be safely used for sanitation purposes within the Universitas Tidar campus environment.